2019
DOI: 10.3390/fermentation5030053
|View full text |Cite
|
Sign up to set email alerts
|

Activity Interactions of Crude Biopreservatives against Spoilage Yeast Consortia

Abstract: It is common to find different spoilage organisms occurring in the same food item, which usually requires food producers to utilize a mixture of synthetic preservatives to control spoilage. This study evaluated the interaction between mixtures of crude biopreservatives against consortia of common spoilage yeasts occurring in beverages. Crude biopreservatives produced from separate yeasts were formulated in different growth inhibition combinations (GICs), i.e., GIC1 (Candida pyralidae Y1117 and Pichia kluyveri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…With a smaller number of variables, RSM can produce a highly accurate response (or output) in non-linear optimisation [90,91]. In addition, RSM can generate a mathematical model in the form of a 3D plot or a second-order polynomial equation, both useful in industrial applications [88,89,97,98]. As a result, it has become a useful tendency to use a coupled bioprocess optimisation approach involving ANNs and RSM in the design of mathematical models and improvement of food production bioprocesses [81][82][83].…”
Section: Bioprocess Optimisation Approaches Using the Concepts Of The 4th Industrial Revolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a smaller number of variables, RSM can produce a highly accurate response (or output) in non-linear optimisation [90,91]. In addition, RSM can generate a mathematical model in the form of a 3D plot or a second-order polynomial equation, both useful in industrial applications [88,89,97,98]. As a result, it has become a useful tendency to use a coupled bioprocess optimisation approach involving ANNs and RSM in the design of mathematical models and improvement of food production bioprocesses [81][82][83].…”
Section: Bioprocess Optimisation Approaches Using the Concepts Of The 4th Industrial Revolutionmentioning
confidence: 99%
“…The health benefits enjoyed by our ancestors in the years gone by are motivating researchers to examine how the same and even better health benefits can be enjoyed today [1,8,20,43,45]. Novel production and bioprocessing methods are being developed to make these foods and their nutrients bioavailable and affordable to produce at a large scale [86][87][88][89]97,98]. Moreover, studies are showing interest in understanding the biological interactions that occur within the entire production and supply chain-from farm to consumer-in order to improve quality, safety and sustainability of the food product [73,99,100].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Such studies have resulted in commercialisation of non- Saccharomyces yeasts including Lachancea thermotolerans , Torulaspora delbrueckii , Metschnikowia pulcherrima and Pichia kluyveri to name a few ( Vejarano and Gil-Calderón, 2021 ). However, more than 40 yeast species have been isolated from grape and wine fermentation environments ( Jolly et al, 2014 ) and recent studies show that some of these have great potential as bioprotectants and biocontrol agents against spoilage organisms ( Kuchen et al, 2019 ; Mewa-Ngongang et al, 2019a ) and phytopathogens ( Bleve et al, 2006 ; Nally et al, 2015 ; Cordero-Bueso et al, 2017 ; Mewa-Ngongang et al, 2019b ; Marsico et al, 2021 ; Sabaghian et al, 2021 ). The most frequently reported yeast antagonists include mainly strains belonging to the Metschnikowia pulcherrima , Hanseniaspora spp., Pichia spp.…”
Section: Introductionmentioning
confidence: 99%
“…A mass of 0.2 g of the annealed powders of Fe-Ag [3:1] RL and Fe-Ag [7:1] Gamma, were immobilized in a 100 µL volume of sterile distilled water and were tested against selected spoilage yeasts. From the resulting mixtures, a volume of 10 µL was spotted in 5 mm diameter and 1.7 mm depth wells created on the test agar plates using an agar driller [4,39]. Before plate inspection for the presence of inhibition zones around the wells, the seeded plates were incubated for 72 h at a temperature of 22 °C.…”
Section: Growth Inhibition Assay and Activity Quantificationmentioning
confidence: 99%
“…This is largely due to the poor handling, and processing including transportation facilities available to producers [2]. Some scholars reported that the yeasts, Dekkera bruxellensis, Dekkera anomala, Zygosaccharomyces bailii, Hanseniaspora uvarum, Candida guilliermondii, Zygosaccharomyces fermentati, Schizosaccharomyces pombe, Debaryomyces hansenii, Saccharomyces cerevisiae, and Zygosaccharomyces florentinus, are responsible for final product spoilage, and are sources of foodborne diseases [3][4][5][6]. This culminates in economic losses [7], noticeable in populated countries such as China, India, USA, Russia, and Nigeria.…”
Section: Introductionmentioning
confidence: 99%